Assessing public support for extending smoke-free policies beyond enclosed public places and workplaces: protocol for a systematic review and meta-analysis - Alex Burdorf; Aziz Sheikh; Jasper V Been; Frank J Van Lenthe; Nienke W Boderie; Famke JM Mölenberg; Wichor M Bramer (BMJ Open)
Introduction Smoke-free enclosed public environments are effective in reducing exposure to secondhand smoke and yield major public health benefits. Building on this, many countries are now implementing smoke-free policies regulating smoking beyond enclosed public places and workplaces. In order to successfully implement such ‘novel smoke-free policies’, public support is essential. We aim to provide the first comprehensive systematic review and meta-analysis assessing levels and determinants of public support for novel smoke-free policies.Methods and analysis The primary objective of this review is to summarise the level of public support for novel smoke-free policies. Eight online databases (Embase.com, Medline ALL Ovid, Web of Science Core Collection, WHO Library Database, Latin American and Caribbean Health Sciences Literature, Scientific Online Library Online, PsychINFO and Google Scholar) will be searched from 1 January 2004 by two independent researchers with no language restrictions. The initial search was performed on 15 April 2020 and will be updated prior to finalisation of the report. Studies are eligible if assessing support for novel smoke-free policies in the general population (age ≥16 years) and have a sample size of n≥400. Studies funded by the tobacco industry or evaluating support among groups with vested interest are excluded. The primary outcome is proportion of public support for smoke-free policies, subdivided according to the spaces covered: (1) indoor private spaces (eg, cars) (2) indoor semiprivate spaces (eg, multi-unit housing) (3) outdoor (semi)private spaces (eg, courtyards) (4) non-hospitality outdoor public spaces (eg, parks, hospital grounds, playgrounds) and (5) hospitality outdoor public spaces (eg, restaurant terraces). The secondary objective is to identify determinants associated with public support on three levels: (1) within-study determinants (eg, smoking status) (2) between-study determinants (eg, survey year) and (3) context-specific determinants (eg, social norms). Risk of bias will be assessed using the Mixed Methods Appraisal Tool and a sensitivity analysis will be performed excluding studies at high risk of bias.Ethics and dissemination No formal ethical approval is required. Findings will be disseminated to academics, policymakers and the general public.